Initial Development and Characterization of PLGA Nanospheres Containing Ropivacaine - Moraes, Carolina Morales; de Matos, Angelica Prado; de Lima, Renata; Rosa, Andre Henrique [UNESP]; de Paula, Eneida; Fraceto, Leonardo Fernandes [UNESP] (Springer, 2007)
Local anesthetics are able to induce pain relief by binding to the sodium channels of excitable membranes, blocking the influx of sodium ions and the propagation of the nervous impulse. Ropivacaine (RVC) is an amino amide, enantiomerically pure, local anesthetic largely used in surgical procedures, which present physico-chemical and therapeutic properties similar to those of bupivacaine but decreased toxicity and motor blockade. The present work focuses on the preparation and characterization of nanospheres containing RVC; 0.25% and 0.50% RVC were incorporated in poly(d,l-lactide-co-glycolide (PLGA) 50:50) nanospheres (PLGA-NS), prepared by the nanoprecipitation method. Characterization of the nanospheres was conducted through the measurement of pH, particle size, and zeta potential. The pH of the nanoparticle system with RVC was 6.58. The average diameters of the RVC-containing nanospheres was 162.7 +/- 1.5 nm, and their zeta potentials were negative, with values of about -10.81 +/- 1.16 mV, which promoted good stabilization of the particles in solution. The cytotoxicity experiments show that RVC-loaded PLGA-NS generate a less toxic formulation as compared with plain RVC. Since this polymer drug-delivery system can effectively generate an even less toxic RVC formulation, this study is fundamental due to its characterization of a potentially novel pharmaceutical form for the treatment of pain with RVC.
Keywords: Ropivacaine; Nanospheres; PLGA; Drug delivery